Constraints on Paleo-Pacific Plate rollback from magmatic spatiotemporal evolution, isotopic composition variations, and crustal thickness changes: Insights from Early Cretaceous adakitic granitoids in the northeastern Asian continental margin - Xinping Li; Yu Dong; Wenchun Ge; Simiao Wang; Junhui Bi; Hao Yang; Jie Tang; Hongying Zhou; Yan Jing; Guochun Zhao (Lithos, 2026)

Manganese Gluconate as a Safe Trace Element Supplement Enhances Immune Function and Resistance to Staphylococcus aureus Infection in Broilers - Changquan Liu; Shuyu Wei; Ming Xu; Mingyang Tao; Youxi Fu; Kexin Liu; Siqi Wang; Simiao Yu; Beiyan Wang; Liquan Yu; Baifen Song; Jinzhu Ma (Biological Trace Element Research, 2026)

Menaquinone-4 protects CD8+ T cells from ferroptosis to enhance anti-tumor immunity - Jiarong Wang; Wen Wang; Simiao Fan; Liyun Liang; Huaibin Hu; Zenqing Song; Yu Zhang; Jiamei Zhang; Wanying Xiao; Biyu Zhang; Yaxin Li; Liang Luo; et al. (Science China Life Sciences, 2026)

Unraveling the structure-selectivity nexus: electrode materials for selective phosphorus removal and recovery via capacitive deionization: A systematic review - Sheng Wen; Yu Ma; Yang Fan; Jinxing Lin; Jiaqi Chen; Simiao Li; Huakun Pan; Xinxi Teng; Shupeng Zhang (Chemical Engineering Journal, 2026)

Application of a thiophene-based conjugated polymer in the photocatalytic eradication of multidrug-resistant bacteria: Synergistic inactivation of MRSA via carboxyl capture and multi-pathway regulation - Ying Xu; Simiao Wang; Xinyu Yu; Yuncong Wang; Lin Han; Yu Wang; Haiyong Guo; Juan Du (Journal of Hazardous Materials, 2025)

Synergistic modulation of sludge hydrolysate-borne bacteria on glycogen accumulation and carbon fixation mechanisms in microalgae - Renjie Li; Yingying Yang; Jiamin Zhao; Simiao Yang; Xiaomin Feng; Jiayu Yu; Xiurong Chen (Environmental Research, 2025)

Performance and mechanism of ciprofloxacin removal in water via catalytic ozonation using Fe-Mg/PDA@Al2O3 - Shanshan Huang; Bolin Li; Gezi Li; Siyuan Zheng; Kanglin Tian; Weimin Xie; Simiao Wu; Jun Wang; Ying Yu; Xiaoman He (Process Safety and Environmental Protection, 2025)

Construction of a thiophene-based conjugated polymer/TP-PCN S-scheme to enhance visible-light-driven photocatalytic activity: Promotion of wound healing in super-resistant bacterial infections - Xin Zhao; Simiao Wang; Jiayu Wang; Xinyue Bai; Zhongwei Yang; Haiyong Guo; Lina Wu; Chunbo Liu; Xin Yu; Juan Du (Journal of Hazardous Materials, 2025)

NH2-MIL-88B(Fe)/PVDF mixed matrix membranes: A one-stone-two-birds strategy for efficient removal of tetracycline hydrochloride from aquatic systems - Simiao Zhao; Hu Zheng; Yuting Xie; Xia Zheng; Ke Liu; Yizhou Yang; Xi Chen; Yuan Xiang; Yu-Hsuan Chiao; Guangyong Zeng (Journal of Environmental Chemical Engineering, 2025)

Late Paleozoic–Early Mesozoic subduction history of Mudanjiang Ocean: New insights from greenschist in the Heilongjiang Complex, NE China - Simiao Wang; Yu Dong; Junhui Bi; Yan Jing; Wenchun Ge; Hao Yang; Jielu Yu; Zheng Ji (Lithos, 2024)

CgIκB2 negatively regulates the expression of interferon-like protein by Rel/NF-κB signal in Crassostrea gigas - Jixiang Niu; Sicong Wang; Xue Qiao; Simiao Yu; Zhuo Yu; Yuhao Jin; Mengyue Huang; Lingling Wang; Linsheng Song (Fish & Shellfish Immunology, 2024)

Innovative insights into organic nitrogen degradation through protein family domains analysis in chicken and pig manure composting using metagenomic sequencing - Lin Zhu; Caihong Huang; Lipin Li; Simiao Wang; Xinxin Wu; Guangchun Shan; Yu Tian (Bioresource Technology, 2024)

Genetic Variability of Mass-Selected and Wild Populations of Yellow Drum (Nibea albiflora) Revealed Using Microsatellites - Qin Yu; Simiao Liu; Qihui Zhu; Ruiyi Chen; Weihua Hu; Dongdong Xu (Fishes, 2024)
In this study, twelve polymorphic microsatellite loci were screened to evaluate the genetic diversity of five yellow drum (Nibea albiflora) populations in the Zhoushan Sea region of the East China Sea, including one wild population (WP), one artificially propagated population (common population, CP), and three breeding populations (parent population, F4; all-female population, AF; and neo-male population, NeoG). The results of genetic diversity analyses showed that all five yellow drum populations had relatively high genetic diversity, with the highest in WP and the lowest in NeoG. Genetic structure analyses showed that the level of genetic differentiation among populations was low, with that between CP and F4 being the largest, whereas that between CP and WP was the smallest. Mutation–drift equilibrium analysis showed that the five populations likely did not experience a recent bottleneck. Our results suggest the CP population was the most suitable for large-scale release for stock enhancement, and precautionary measures shall be taken for the AF population before it is used for cage culture to avoid potential genetic concerns of the wild population. Nevertheless, further genetic diversity monitoring is needed to evaluate genetic effects and avoid the negative impact of excessive genetic differentiation between breeding and wild populations.

Stearic acid-modified hollow hydroxyapatite particles with enhanced hydrophobicity for oil adsorption from oil spills - Farishta Shafiq; Chenyu Liu; Hengjun Zhou; Hailiang Chen; Simiao Yu; Weihong Qiao (Chemosphere, 2024)

The immune enhancement effect of CpG-ODNs on the vaccine of inactivated Vibrio harveyi in tiger puffer (Takifugu rubripes) - Simiao Yu; Lei Gao; Zhen Geng; Wei Wu; Xuejie Lin; Ruijun Li; Shigen Ye; Lingling Wang; Linsheng Song (Aquaculture, 2023)

An ATP-binding cassette transporter G2 (CgABCG2) regulates the haemocyte proliferation by modulating the G1/S phase transition of cell cycle in oyster Crassostrea gigas - Simiao Yu; Xue Qiao; Ying Yang; Xiaoyu Gu; Wending Sun; Xiyang Liu; Dan Zhang; Lingling Wang; Linsheng Song (Fish & Shellfish Immunology, 2023)

Effect of dietary oregano oil on growth performance, disease resistance, intestinal morphology, immunity, and microbiota of hybrid grouper (Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂) - Yu Xin; Hao Liu; Xiaobo Yan; Weibin Huang; Simiao Pan; Menglong Zhou; Baiquan Lu; Beiping Tan; Xiaohui Dong; Yuanzhi Yang (Frontiers in Marine Science, 2022)
The study aimed to investigate the effects of oregano oil (OO) supplement in the diet on the growth performance, disease resistance, immunity, and intestinal health of hybrid grouper. Six isonitrogenous and isolipidic diets were fed to the grouper with an initial weight of 19.10 ± 0.12 g for 8 weeks, of which the dietary OO levels were 0 (Control), 0.1 (OO-0.1), 0.3 (OO-0.3), 0.6 (OO-0.6), 0.9 (OO-0.9), or 1.2 (OO-1.2) g kg -1 . The results showed that there were no significant differences in growth performance among the six groups, while the OO supplement could improve the disease resistance ability of grouper. Our findings have demonstrated that the OO supplement, especially 0.3 g kg -1 , could improve the intestinal morphology via increasing the villus number and muscle thickness and elevate digestive enzyme activities such as those of amylase (AMS) and lipase. The 0.3-g kg -1 OO supplement also can activate the antioxidant defense system, reduce nuclear factor erythroid 2-related factor 2-like 2 (Nrf2)/Kelch-like-ECH-associated protein 1 (Keap1) expression, and then enhance the immune ability via acid phosphatase (ACP), lysozyme (LYS), complement C3 (C3), and tight junction-associated signaling pathways in hybrid grouper. Meanwhile, the relative abundance of Firmicutes and Bacteroidetes in the OO-0.3 group was significantly higher than that of Control group ( P < 0.05), while the relative abundance of Proteobacteria showed a basically opposite trend ( P < 0.05). These findings suggested that dietary OO supplementation could significantly improve intestinal health and induce the antioxidant defense system and immunity, which means that OO could be used as a functional feed additive to protect the intestine, and the appropriate addition level of OO should be 0.3 g kg -1 .

The generation of biogenic manganese oxides and its application in the removal of As(III) in groundwater - Guannan Liang; Yu Yang; Simiao Wu; Yonghai Jiang; Yunfeng Xu (Environmental Science and Pollution Research, 2017)